2018
DOI: 10.1186/s12864-018-5216-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Robertsonian fusion in Solea senegalensis (Kaup, 1858) revealed by zoo-FISH and comparative genome analysis

Abstract: BackgroundSolea senegalensis (Kaup, 1858) is a commercially important flatfish species, belonging to the Pleuronectiformes order. The taxonomy of this group has long been controversial, and the karyotype of the order presents a high degree of variability in diploid number, derived from chromosomal rearrangements such as Robertsonian fusions. Previously it has been proposed that the large metacentric chromosome of S. senegalensis arises from this kind of chromosome rearrangement and that this is a proto-sex chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 50 publications
(69 reference statements)
3
31
0
Order By: Relevance
“…The hybridizations agree with the results obtained for the BAC clones tlr8, calr, lysg and mx that had already been located (Ponce et al, 2011; García-Cegarra et al, 2013; Merlo et al, 2017; García-Angulo et al, 2018). In our study, candidate genes tlr3 and tlr8 were found in different chromosomes.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The hybridizations agree with the results obtained for the BAC clones tlr8, calr, lysg and mx that had already been located (Ponce et al, 2011; García-Cegarra et al, 2013; Merlo et al, 2017; García-Angulo et al, 2018). In our study, candidate genes tlr3 and tlr8 were found in different chromosomes.…”
Section: Discussionsupporting
confidence: 88%
“…Of the 14 BAC clones analyzed, nine BAC clones were sequenced with a total of 80 genes annotated, and the other five BAC clones had been sequenced previously (Ponce et al, 2011; García-Cegarra et al, 2013; Merlo et al, 2017; García-Angulo et al, 2018). In total, 109 genes were annotated and 24 of the 109 genes (22.01%) were found to be related to the immune system (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…rhombus , which present a karyotype with 2n = 44 chromosomes including two metacentric pairs [ 31 ]. The origin of this chromosome has also been confirmed by Zoofish data obtained from two species of the Soleidae family ( Dicologlossa cuneata and Dagetichthys lusitanica ), and by comparative genome analysis with Cynoglossus semilaevis [ 32 ].…”
Section: Introductionmentioning
confidence: 78%
“…To investigate the structure of the dmrt1 gene in the genome, a BAC sequence from clone 48K7 [ 32 ] was used. The dmrt1 cDNA of S .…”
Section: Resultsmentioning
confidence: 99%